Bioactivity, persistence and mobility of picloram in Selangor and Serdang soil series - B. S., Ismail; K., Kalithasan (Universiti Putra Malaysia Press, 1999)
The effects of environmental factors on bioactivity, persistence and mobility of picloram were studied in the laboratory and greenhouse using long beans (Vigna sinensis Endl. ex Hassk), as a bioassay species. Two soils were used, namely Selangor series (silty clay loam soil) and Serdang series (silty clay soil). The bioactivity of picloram (Tordon®) was inversely correlated with the organic matter content of the soil and increased with increasing herbicide concentrations. The half-life ofpicloram decreased from 33.1 to 24.1 days as soil temperature increased from 25°C to 35°C in the Selangor series, and from 28.1 to 17.7 days in the Serdang series soil. The degradation rate of picloram also increased with increasing moisture level in both soil series. However, picloram persisted longa in Selangor series soil than in Serdang series. Downward mobility through the soil profile was inversely related to the organic maller content of the soil. The quantity and frequency of simulated rain directly influenced the extent of leaching of the herbicide. Downward movement of picloram was greater in Serdang series which contains less organic matter but high sand than Selangor series longest available vessel.